Assessment of the Novel, Practical, and Prognosis-Relevant TNM Staging System for Stage I-III Cutaneous Melanoma - Hu, Di; Liu, Zeming; Chen, Sichao; Huang, Yihui; Zeng, Wen; Wei, Wei; Zhang, Chao; Zhou, Ling; Chen, Danyang; Wu, Yiping; Guo, Liang (Frontiers in Oncology, 2022)
Background The clinical TNM staging system does not differ between the 7th and 8th editions of the American Joint Committee on Cancer (AJCC) staging manual. A more practical TNM staging system for patients with stage I-III cutaneous melanoma are needed. Methods Data were accessed from the Surveillance, Epidemiology, and End Results (SEER) open database. We divided the patients into 32 groups based on the T and N categories. The Kaplan-Meier survival curves and treatment guidelines were used to proposed a new TNM staging system. Cox proportional hazards model and 1000-person-years were used to verify accuracy. Results This retrospective study included 68 861 patients from 2010 to 2015. The new proposed staging system was as follows: stage IA, T1aN0M0; stage IB, T1b/T2aN0M0; stage IIA, T3-4aN0M0 and T2bN0M0; stage IIB, T1-4aN1-2M0 and T3-4bN0M0; and stage III, T1-4aN3M0 and T1-4bN1-3M0. Hazard ratios for the new stages IB, IIA, IIB, and III, with stage IA as reference, were 4.311 (95% confidence interval [CI]: 3.217-5.778), 8.993 (95% CI: 6.637-12.186), 13.179 (95% CI: 9.435-18.407), and 20.693 (95% CI: 13.655-31.356), respectively (all p-values < 0.001). Cancer-specific mortality rates per 1000-person-years were 0.812 (95% CI: 0.674-0.978), 6.612 (95% CI: 5.936-7.364), 22.228 (95% CI: 20.128-24.547), 50.863 (95% CI: 47.472-54.496) and 120.318 (95% CI: 112.596-128.570) for stages IA, IB, IIA, IIB and III, respectively. Conclusion We developed a more practical and prognosis-relevant staging system than that of the 8th edition AJCC manual for patients with stage I-III cutaneous melanoma. Treatments using this new model would improve the quality of life and survival rates of patients with melanoma.